2019
DOI: 10.1016/j.ajog.2018.12.022
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of contraceptive switching and discontinuation within the first 6 months of use among Highly Effective Reversible Contraceptive Initiative Salt Lake study participants

Abstract: BACKGROUND: Nearly half of women will switch or discontinue using their selected contraceptive method in the first year. Research on early switching or discontinuation provides important clinical and public health insights, although few studies have assessed associated factors, particularly among longitudinal cohorts. OBJECTIVE: The current study explores attributes associated with early contraceptive method switching or discontinuation (<6 months of initiation) among participants enrolled in the intervention … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
40
1
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(52 citation statements)
references
References 25 publications
8
40
1
3
Order By: Relevance
“…Adjusted hazard ratio of COCs and DMPA were signi cant in multivariable Cox proportional hazard model. These results were consistent with previous clinical studies [13,14]which showed signi cant lower contraceptive discontinuation among women who used LARC compared to the other methods. However, the rates of contraceptive discontinuation during the one-year period for all four types of contraceptives in this study were quite low.…”
Section: Discussionsupporting
confidence: 92%
“…Adjusted hazard ratio of COCs and DMPA were signi cant in multivariable Cox proportional hazard model. These results were consistent with previous clinical studies [13,14]which showed signi cant lower contraceptive discontinuation among women who used LARC compared to the other methods. However, the rates of contraceptive discontinuation during the one-year period for all four types of contraceptives in this study were quite low.…”
Section: Discussionsupporting
confidence: 92%
“…However, just like our study, the probability of continuation of an initiated contraceptive method was higher for the voucher cohort versus the nonvoucher cohort at 6 months. Although the inclusion/provision of information about family planning benefits and possible side effects on the voucher could have been helpful in continuously reminding women about expectations from the different contraceptive methods chosen [41], qualitative data analysis of interviews conducted with a subset of participants to understand how the voucher (information-on-voucher, counseling, time-bound, waiting time, methods administration) facilitated decision-making, initiation, and/or continuous use of contraception among these child-bearing WLWH is underway. Twelve-month postpartum data collection is still ongoing.…”
Section: Discussionmentioning
confidence: 99%
“…Contraceptives improve both public health and individual lives [ 1 , 2 ], but many people use contraceptives inconsistently or not at all due to method dissatisfaction [ 3 ], and many stop using their methods after only several months [ [4] , [5] , [6] , [7] ]. While not inherently negative, discontinuation can be indicative of less-than-ideal method selection due to availability, cost or other barriers.…”
Section: Introductionmentioning
confidence: 99%